The present and the Archaic River Valley morphology and groundwater condition in the Plaosan Temple complex Central Java-Indonesia - Eko Haryono; J. Susetyo Edy Y; Imam Fauzi; Didik S; Wahyu Broto R (Indonesian Journal of Geography, 2004)
The Plaosan Temple which was built during the eighth and tenth century AD is one of four temple complexes in the Prambanan area, Central Java-Indonesia. On going excavation in the temple complex discloses the occurrence of canals along the outer fences. The canals are eight meters wide and four meters deep. This article aims at reconstructing archaic river course and groundwater condition due to the construction of the canals. Aerial photo interpretation, excavation, ground water level measurement and valley morphology measurement reveal an anomaly of the nearest river in the temple complex. The river had seemingly been bypassed south-eastward to its tributary just before entering Plaosan Temple complex. Groundwater level dropped and its flow direction changed from nearly southward to south-eastward direction. These phenomena indicate that the canals were groundwater-discharged canals.